1993
DOI: 10.1137/0406030
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Edge Dominating Sets

Abstract: Let G (V, E) be a finite undirected graph with n vertices and m edges. A minimum edge dominating set of G is a set of edges D, of smallest cardinality 3"(G), such that each edge of E D is adjacent to someThe edge domination problem is NP-complete for planar bipartite graphs, their subdivision, line, and total graphs, perfect claw-free graphs, and planar cubic graphs. The stable set problem and the edge domination problem are NP-complete for iterated total graphs.The edge domination problem is solvable in O(n 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 14 publications
0
62
0
Order By: Relevance
“…By Proposition 3, MIN-POM belongs to NP. To show NP-hardness, we give a reduction from the NP-complete restriction of MMM to subdivision graphs [6] (given a graph G, the subdivision graph of G is obtained by subdividing each edge e = {u, w} into two edges {u, v e }, {v e , w}, where v e is a new vertex corresponding to e).…”
Section: Theorem 2 Min-pom Is Np-completementioning
confidence: 99%
“…By Proposition 3, MIN-POM belongs to NP. To show NP-hardness, we give a reduction from the NP-complete restriction of MMM to subdivision graphs [6] (given a graph G, the subdivision graph of G is obtained by subdividing each edge e = {u, w} into two edges {u, v e }, {v e , w}, where v e is a new vertex corresponding to e).…”
Section: Theorem 2 Min-pom Is Np-completementioning
confidence: 99%
“…The problem of focus in our paper is the maximal independent edge set problem (Cormen et al, 2009) wherein we want to find the largest set of independent edges such that no two edges have a common end vertex. Note that heuristics (Horton & Kilakos, 1993) for the minimum edge dominating set problem cannot be applied to determine the maximal a(di)ssortative matching. Because, heuristics for the minimum edge set problem are more likely to determine the set of edges such that each edge in the set covers a larger number of adjacent edges.…”
Section: Related Workmentioning
confidence: 99%
“…It is equivalent to the problem of finding a minimum edge dominating set (Horton & Kilakos, 1993) -to find the smallest set of edges of the graph such that each edge in the set covers itself and covers one or more adjacent edges as well as satisfies the matching constraint (no two edges in the set have a common end vertex). The problem of focus in our paper is the maximal independent edge set problem (Cormen et al, 2009) wherein we want to find the largest set of independent edges such that no two edges have a common end vertex.…”
Section: Related Workmentioning
confidence: 99%
“…Another consequence of our results is. In [11], it was shown that STABLE SET is NP-complete on squares of the subdivision of some graph (i.e. the squares of the total graph of some graph).…”
Section: Further Considerationsmentioning
confidence: 99%